(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This lesson plan is designed for an English language class, focusing on the highly relevant global issue of Environmental Protection. The main objective is to enhance students’ communicative competence in English while engaging them in a critical discussion about the roles and responsibilities of young people in combating climate change, pollution, and resource depletion. The session aims to integrate vocabulary related to ecology and sustainability, encourage critical thinking, and motivate practical actions through discussions, case studies, and presentation of solutions.